Adaptive delay scheduling algorithm based on data center load analysis - JIN Jia-hui; LUO Jun-zhou; SONG Ai-bo; DONG Fang (Tongxin xuebao)
Current delay scheduling algorithms,based on static waiting time threshold,can not adapt to dynamic load of a data center.To address this issue,an adaptive waiting time threshold model was proposed.Based on this model,an adap-tive delay scheduling algorithm（ADS） was designed.ADS adjusts jobs’ waiting time threshold dynamically to reduce the job response time,according to the information of idle servers’ arrival intensity,available network bandwidth and job running status.A prototype system using ADS was developed,on which the validation of the adaptive waiting time threshold model and the evaluation of ADS’s performance were carried out.It is shown that ADS outperforms previous delay scheduling algorithms in term of the job response time.